The Prosody of Harar Oromo Nouns - Majed Al Solami (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
This paper examines the tone in Harar Oromo, a language widely spoken in Ethiopia. The focus is on tone in nouns. The examination implements acoustic analysis of tone using pitch contours, which helps in determining the type and position of tone in roots and in nominative and accusative case. The results show that roots can have either L or H tone, while case suffixes always have H tone. This suggests that tone is predictable in suffixes, but not in roots. The analysis suggests that Harar Oromo has a restricted tone system that is similar to stress-like languages.